Intrauterine Infections: Modern View upon the Problem - V. A. Tsinzerling (Журнал инфектологии, 2014)
In the paper are discussed the long-term results of the author and his collaborators, as well as literary data. The questions of classification of intrauterine infections (IUI) are discussed and the principles of their laboratory and morphological diagnostics. Original charts of different variants of intrauterine infect are cited. Brief characteristics of well and less known etiological forms of IUI are presented. Special attention is devoted to different clinical outcomes of intrauterine infect: starting with preterm stillbirth till apparently healthy baby with latent infection which can unfavorable influence upon the course of different pathological processes much later. The questions which need further complex study are formulated.